2002
DOI: 10.2118/80287-pa
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Interpretation of Long-Term Data Acquired From Permanent Pressure Gauges

Abstract: Summary Long-term data from permanent gauges have the potential to provide more information about a reservoir than data from traditional pressure-transient tests that last for a relatively small duration. Besides reducing ambiguity and uncertainties in the interpretation, long-term data also provide an insight on how reservoir properties may change as the reservoir is produced. This study developed a multistep procedure for the processing and interpretation of long-term pressure data. The proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…In addition to analyzing the seismic data which were one of the prime motivations for developing the WT, the applications also include numerical simulation of flow and transport equations [62], upscaling of a conductivity or permeability field [26,60,82], pressure transient analysis [5,25,28,47,87], upscaling of miscible displacements in heterogeneous porous media [27], reservoir characterization [11,55,59,63,66], identification of the fracture density along wells in oil and gas reservoirs [81], as well as problems involving turbulent transport and chemical reactions in the atmosphere [38]; for a recent review, see [78,80].…”
Section: Wavelet Scale Up Of the Single-phase Permeabilitiesmentioning
confidence: 99%
“…In addition to analyzing the seismic data which were one of the prime motivations for developing the WT, the applications also include numerical simulation of flow and transport equations [62], upscaling of a conductivity or permeability field [26,60,82], pressure transient analysis [5,25,28,47,87], upscaling of miscible displacements in heterogeneous porous media [27], reservoir characterization [11,55,59,63,66], identification of the fracture density along wells in oil and gas reservoirs [81], as well as problems involving turbulent transport and chemical reactions in the atmosphere [38]; for a recent review, see [78,80].…”
Section: Wavelet Scale Up Of the Single-phase Permeabilitiesmentioning
confidence: 99%
“…Hu et al (2006) found band-pass filtering using wavelets effective at identifying the amplitude and frequency of atmospheric tides. In a more general reservoir engineering context, Athichanagorn et al (2002) applied wavelet analysis to reduce the ambiguity and uncertainty in long-term subsurface data by identifying outlying data points and filtering unwanted noise before assessing aquifer parameters using the filtered data. Leaver (2006) undertook a comparative study of spectral analysis on data from three geothermal fields.…”
Section: Significant Developments In the Analysis Of Periodic Disturbmentioning
confidence: 99%
“…In the last two decades, wavelet transform has appeared several times in the petroleum engineering for detecting changes in flow rate, transient identification, de-noising and up-scaling of reservoir properties [13][14][15]. Kikani and He used the wavelet transform for data de-noising and transient detection among synthetic pressure transient data [13].…”
Section: Introductionmentioning
confidence: 99%
“…Kikani and He used the wavelet transform for data de-noising and transient detection among synthetic pressure transient data [13]. Athichanagorn et al developed a wavelet based model for pre-processing and interpretation both long-term simulated as well as actual field data [14]. Olsen and Nordtvedt investigated the wavelet transform ability for filtering and noises removal from production data [15].…”
Section: Introductionmentioning
confidence: 99%